Local and Regional Scale Heterogeneity Drive Bacterial Community Diversity and Composition in a Polar Desert - Feeser, Kelli L.; Van Horn, David J.; Buelow, Heather N.; Colman, Daniel R.; McHugh, Theresa A.; Okie, Jordan G.; Schwartz, Egbert; Takacs-Vesbach, Cristina D. (Frontiers in Microbiology, 2018)
The distribution of organisms in an environment is neither uniform nor random but is instead spatially patterned. The factors that control this patterning are complex and the underlying mechanisms are poorly understood. Soil microbes are critical to ecosystem function but exhibit highly complex distributions and community dynamics due in large part to the scale-dependent effects of environmental heterogeneity. To better understand the impact of environmental heterogeneity on the distribution of soil microbes, we sequenced the 16S rRNA gene from bacterial communities in the microbe-dominated polar desert ecosystem of the McMurdo Dry Valleys (MDV), Antarctica. Significant differences in key edaphic variables and alpha diversity were observed among the three lake basins of the Taylor Valley (Kruskal-Wallis; pH: chi-square = 68.89, P < 0.001, conductivity: chi-square = 35.03, P < 0.001, observed species: chi-square = 7.98, P = 0.019 and inverse Simpson: chi-square = 18.52, P < 0.001) and each basin supported distinctive microbial communities (ANOSIM R = 0.466, P = 0.001, Random Forest ratio of 14.1). However, relationships between community structure and edaphic characteristics were highly variable and contextual, ranging in magnitude and direction across regional, basin, and local scales. Correlations among edaphic factors and the relative abundance of specific phyla were most pronounced along local environmental gradients in the Lake Fryxell basin where Acidobacteria, Bacteroidetes and Proteobacteria declined while Deinococcus-Thermus and Gemmatimonadetes increased with soil conductivity (all P < 0.1). Species richness was most strongly influenced by the soil conductivity gradient present within this study system. We suggest that the relative importance of pH versus soil conductivity in structuring microbial communities is related to the length of edaphic gradients and the spatial scale of sampling. These results highlight the importance of conducting studies over large ranges of key environmental gradients and across multiple spatial scales to assess the influence of environmental heterogeneity on the composition and diversity of microbial communities.